Molecular Mechanisms of Diaphragm Myopathy in Humans With Severe Heart Failure. Issue 6 (4th February 2021) - Mangner, Norman; Garbade, Jens; Heyne, Estelle; van den Berg, Marloes; Winzer, Ephraim B.; Hommel, Jennifer; Sandri, Marcus; Jozwiak-Nozdrzykowska, Joanna; Meyer, Anna L.; Lehmann, Sven; Schmitz, Clara; Malfatti, Edoardo; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Diaphragm weakness impairs quality of life, exercise capacity, and survival in patients with chronic heart failure (CHF) and reduced left ventricular ejection fraction. However, the underlying cellular mechanisms responsible in humans remain poorly resolved. Objectives: We prospectively evaluated clinical, functional (in vivo/in vitro), histological/ultrastructural, and molecular alterations of the diaphragm from patients with CHF receiving a left ventricular assist device compared with patients without CHF undergoing elective coronary bypass grafting (control) in the observational LIPAMUS-HF (Lipsia Diaphragm And Muscle Heart Failure). Methods and Results: Participants (controls=21, CHF=18) underwent cardiopulmonary exercise and spirometry/respiratory muscle testing alongside diaphragm and cardiac imaging. Diaphragm biopsies were phenotyped for mitochondrial respiration, muscle fiber function, histology/ultrastructure, and protein expression. In vivo respiratory muscle function and diaphragm thickness were reduced in CHF by 38% and 23%. Diaphragm biopsies revealed a fiber-type shift and severe fiber atrophy in CHF alongside elevated proteasome-dependent proteolysis (ie, MuRF1 [muscle-specific RING finger protein 1] expression, ubiquitination, ubiquitin-proteasome activity) and myofibrillar protein oxidation, which corresponded to upregulated Nox (NADPH [nicotinamide adenine dinucleotide phosphate oxidase] oxidase; Nox2/Nox4) signaling. Mitochondria demonstrated severe intrinsic functional and ultrastructural abnormalities in CHF characterized by accumulation of small mitochondria and inhibited autophagy/mitophagy. Single muscle fiber contractile function revealed reduced Ca 2+ sensitivity in CHF and there was evidence of RyR1 (ryanodine receptor 1) dysfunction indicating Ca 2+ leak from the sarcoplasmic reticulum. Mitochondrial and Ca 2+ measures corresponded to upregulated Nox4 isoform NADPH oxidase expression. Molecular markers correlated to whole-body exercise intolerance and diaphragm dysfunction/wasting. Conclusions: Patients with CHF demonstrate an obvious diaphragm myopathy independent of disuse or other confounding factors, such as aging, obesity, or hypertension. Diaphragm weakness in CHF was associated with intracellular abnormalities characterized by fiber atrophy, oxidative stress, mitochondrial dysfunction, impaired Ca 2+ homeostasis, elevated proteasome-dependent proteolysis, but inhibited autophagy/mitophagy, which we speculate offers a novel therapeutic molecular target regulated by a Nox-MuRF1/ubiquitin-proteasome-mitochondria-RyR1/Ca 2+ signaling axis. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02663115.